Functional analysis of the group specific interactions between AIP and AgrC in Staphylococcus aureus - Jensen, Rasmus O. (2009)
Staphylococcus aureus is an important human pathogen. The emergence of multiple antibiotic resistant bacteria and lack of new antibiotics has highlighted the need for better understanding of staphylococcal physiology, molecular biology and virulence. In S. aureus the agr quorum sensing (QS) system is a global regulator of virulence. In the agr system an autoinducing peptide (AIP) activates the histidine protein kinase (HPK), AgrC, leading to a switch from the production of colonization factors to exotoxins. The S. aureus agr system has diverged such that there are four different agr groups, each with a distinct AIP capable of activating its cognate AgrC but inhibiting the AgrC of the other groups. To investigate the molecular basis for the recognition of AIPs by AgrC, transmembrane topology modelling together with site-specific mutagenesis were used. The transmembrane topology of AgrC was predicted to consist of six transmembrane helices (TMHs) and three extracellular loops with both the N- and C-terminals on the cytoplasmic side. Since AIP-1 and AIP-4 differ by a single amino acid residue, the S. aureus AgrC1 and AgrC4 proteins were compared to identify extracellular amino acids likely to be involved in AIP recognition. Site-specific mutagenesis was used to exchange the key AgrC1 and AgrC4 amino acid residues in extracellular loops 1 and 2. The response of these AgrC mutants was evaluated using a novel bioluminescent AIP reporter. The data obtained showed that differential recognition of AIP-1 and AIP-4 depend primarily on three amino acid residues in loop 2, but that loop 1 plays an essential for activation but not for inhibition of AgrC. The data obtained also revealed that a single mutation in the AgrC1 loop2 results in conversion of (ala5)AIP-1 from a potent antagonist to an activator, essentially forcing the evolution of a fifth agr group.